GREENHOUSE GAS EMISSIONS AS AN IMPACT OF NEW ROAD UNDER RAILWAY ELEVATION PROJECT IN TAOYUAN, TAIWAN - Rahayu Kusumaningrum (Prokons: Jurnal Teknik Sipil, 2017)
Frequent occurrence of severe traffic congestion between Taoyuan City and Zhongli City has encouraged Taoyuan County Government to build elevated railway between these two cities. Besides, this plan also intended to merge all road signage by constructing new roads under the newly built elevated railway. Based on the environmental point of view, railway infrastructure improvement may be able to reduce the congestion and also emission. But the construction of new roads under it may result conversely, especially for the area neighboring the project. Therefore, the impact of railway elevation project parallel with the construction of new road on greenhouse gas emissions generated by road transport needs to be further studied.This study integrates transportation planning model and emission estimation model in order to estimate CO2 emissions as an impact of road improvement and further shows the spatial distribution of emission in grid-based emission. Short-term and long-term period analysis were done both for Taoyuan County and the affected area. Short-term period analysis analyze the project’s impact on emission for short-term after the project is implemented. Meanwhile, long-term period analysis analyze the impact of the project 20 years later.The results shows that in term of emission, the implementation of railway elevation project parallel with the construction of new roads generates the lowest CO2 emissions for whole Taoyuan County area both for short-term and long-term period analysis. In contrary, for project-affected area, the lowest emission is derived from the implementation of railway elevation project without construction of new roads both for short-term and long-term period analysis. Keywords: Railway elevation project, road improvement, emission estimation model, grid-based emission, Taoyuan County